Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1302/2046-3758.82.bjr-2018-0146.r1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a calcium sulphate bone void filler on the third-body damage and polyethylene wear of total knee arthroplasty

Abstract: Objectives Bone void fillers are increasingly being used for dead space management in arthroplasty revision surgery. The aim of this study was to investigate the influence of calcium sulphate bone void filler (CS-BVF) on the damage and wear of total knee arthroplasty using experimental wear simulation. Methods A total of 18 fixed-bearing U2 total knee arthroplasty system implants (United Orthopedic Corp., Hsinchu, Taiwan) were used. Implants challenged with CS-BVF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Scratching the counterfaces with a diamond stylus allowed the geometry of the scratches to be more closely controlled. Previous studies have shown the lip height of scratches on retrieved hip and knee implants to be in the range of 0.01-4.1 µm [25,26] and experimental studies have shown larger scratch lip heights, up to 4 µm, to increase the wear of both hip [27] and knee implants [28]. To create a scratch of the same lip height in PEEK, a lower axial load was applied to the diamond stylus against the PEEK plates compared to CoCr due to the lower hardness of the PEEK polymer (Table A1) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Scratching the counterfaces with a diamond stylus allowed the geometry of the scratches to be more closely controlled. Previous studies have shown the lip height of scratches on retrieved hip and knee implants to be in the range of 0.01-4.1 µm [25,26] and experimental studies have shown larger scratch lip heights, up to 4 µm, to increase the wear of both hip [27] and knee implants [28]. To create a scratch of the same lip height in PEEK, a lower axial load was applied to the diamond stylus against the PEEK plates compared to CoCr due to the lower hardness of the PEEK polymer (Table A1) [18].…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 53 Cone fracture 54 underneath the tibial insert is another failure mode seen in mobile designs but rarely found in fixed-bearing knees. Further investigation is required to understand whether novel biomaterials could reduce implant wear in TKA 55 or reduce the incidence of component breakage.…”
Section: Discussionmentioning
confidence: 99%
“…Pubic symphysis osteomyelitis is a rare complication following urological surgery (Kahokehr et al, 2020;Lavien et al, 2017;Nosé et al, 2020). Bony infection of the pubic symphysis following urological surgery typically presents with pain in the groin or paramidline over the pubis with tenderness with or without purulent drainage from previous incisions (Burns and Gregory, 1977;Del Busto et al, 1982;Gupta et al, 2015). Additionally, patients may have difficulty or pain with ambulation over the pubic symphysis (Devlieger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients may have difficulty or pain with ambulation over the pubic symphysis (Devlieger et al, 2020). In acute cases of osteomyelitis, there may be elevated C-reactive protein (CRP), leukocytosis, and elevated erythrocyte sedimentation rate (ESR) (Del Busto et al, 1982;Gupta et al, 2015). However, in chronic osteomyelitis, there is a compromised local or systemic immune response, and inflammatory markers may not be elevated (Cierny et al, Cierny and DiPasquale, 2006;Panteli and Giannoudis, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation